2016
DOI: 10.9775/kvfd.2016.15668
|View full text |Cite
|
Sign up to set email alerts
|

Kaz (Anser anser) ve Tavuk (Gallus gallus domesticus) Yumurta Kabuğunun Embriyonik Gelişim Sırasında Taramalı Elektron Mikroskop ile Karşılaştırılması

Abstract: The purpose of this study was to examine the comparative differences of eggshell structure between geese and chickens during embryonic development by SEM. Goose eggs and chicken eggs were used for the study. Eggs of each species were divided into three groups: The eggs within first group were used subsequent to collection, those of second group were collected during the mid-point of incubation and those of third group were collected at the end of the incubation. The eggshells samples with dimensions of 0.5 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…2016). There was no significant change in shell thickness during incubation in geese and hens (Bingöl et al 2016, Yildirim 2018. No significant change in the shell thickness of 1year-old geese was found when compared to other ages (Tilki and İnal 2004).…”
Section: Introductionmentioning
confidence: 71%
“…2016). There was no significant change in shell thickness during incubation in geese and hens (Bingöl et al 2016, Yildirim 2018. No significant change in the shell thickness of 1year-old geese was found when compared to other ages (Tilki and İnal 2004).…”
Section: Introductionmentioning
confidence: 71%
“…The observations of Bingol et al. (2016) were quite cursory and showed no differences between the eggshell microstructure and ultrastructure of chicken and goose. Other, more detailed studies of eggshell structure (including the orientation of calcium carbonate crystals) in guinea fowl and geese showed significant differences between these species (Pérez‐Huerta & Dauphin, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…The research of avian eggshells microstructure and ultrastructure is mainly concerned with domesticated birds (Bingol et al, 2016;P erez-Huerta & Dauphin, 2016). The observations of Bingol et al (2016) were quite cursory and showed no differences between the eggshell microstructure and ultrastructure of chicken and goose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations